TRENDS IN POULTRY CONSUMPTION AFTER POLAND’S ACCESSION TO THE EUROPEAN UNION - Trajer, Marzena; Mieczkowski, Martyn (Proceedings of the International Scientific Conference "Economic Sciences for Agribusiness and Rural Economy", 2018)
The poultry industry is one of the most rapidly developing sectors of the national agriculture, and Poland is the largest poultry producer in the European Union. Since Poland’s accession to the European Union, the two main factors determining the development of the poultry industry in Poland have been export demand and the growing domestic consumption. The aim of this article was to analyse the changes in the balance sheet of poultry consumption in Poland in the context of conditions of the poultry market and to analyse the impact of changes in red meat consumption on changes in the dynamics of poultry consumption.